Pengaruh Student Team Achievement Division (STAD) terhadap Pengetahuan dan Sikap Mencegah Merokok Siswa Madrasah Aliyah Pondok Pesantren Nurul Qarnain Sukowono Jember (The Effect of Student Team Achievement Division (STAD) towards Knowledge and Attitude i - Feri Ekaprasetia; Dodi Wijaya; Erti Ikhtiarini Dewi (Pustaka Kesehatan, 2014)
Teenagers’ knowledge and attitude in preventing smoking becomes the factor of teenager to smoke. One of the ways to improve teenagers’ knowledge and attitude is doing education about health which is delivered using Student Team Achievement Division (STAD) method. Kind of experiment used is quasy experimental with non equivalent control group plan.Sampling method using multistage random sampling with the total respondent is 48 which consist of 24 control group and 24 intervention group. The result of analyzing data using Wilcoxon test is P value knowledge = 0,013 and P value attitude = 0,005 whereas the comparison between control group and intervention group using Mann Whitney test is P value knowledge and attitude is 0,000 and observing the degree of guiltiness (α = 0,05) so P value < 0,05. The analysis result is knowledge variable 22 respondents (91,7%) have high knowledge, 2 respondents (8,3%) average knowledge and none of the respondents which have low knowledge after being done intervention. In attitude variable, 12 respondents (50%) have good attitude, 12 respondents (50%) have average attitude and none of the respondents which have bad attitude after being done intervention. The conclusion is there are meaningful effects of STAD to the knowledge and attitude of preventing smoking to the teenagers of MA Nurul Qarnain and knowledge and attitude have diferented betwen experiment group and control group. Keywords : STAD, knowledge, attitude, smoking, teenagers